2021
DOI: 10.1111/andr.13038
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of four sperm preparation techniques on sperm motility, morphology, DNA fragmentation, acrosome status, oxidative stress, and mitochondrial activity: A prospective study

Abstract: Background: Suboptimal human semen handling in vitro may induce sperm damage.However, the effects of semen swim-up, pellet swim-up, density gradient, and density gradient followed by SU on sperm motility, morphology, DNA fragmentation, acrosome reaction, intracellular reactive oxygen species, and mitochondrial activity were not fully understood.Objectives: To study the impact of four sperm preparation techniques on sperm functional parameters. Materials and methods:This study was conducted on 60 infertile men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 101 publications
0
17
0
Order By: Relevance
“…The sperm acrosome contains many hydrolytic enzymes that are closely related to fertilization, and acrosome integrity facilitates the fertilization process (van der Horst, 2021). Several mitochondria are distributed at the neck of the sperm, which provides energy for sperm metabolism and movement, and participate in several fertilization processes, such as sperm hyperactivation, capacitation, and acrosome reaction (Nesci et al, 2020;Raad et al, 2021). Additionally, ROS is the main free radical in sperm cells.…”
Section: Discussionmentioning
confidence: 99%
“…The sperm acrosome contains many hydrolytic enzymes that are closely related to fertilization, and acrosome integrity facilitates the fertilization process (van der Horst, 2021). Several mitochondria are distributed at the neck of the sperm, which provides energy for sperm metabolism and movement, and participate in several fertilization processes, such as sperm hyperactivation, capacitation, and acrosome reaction (Nesci et al, 2020;Raad et al, 2021). Additionally, ROS is the main free radical in sperm cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the latter is less efficient than SU in selecting sperm cells with intact DNA [ 66 ]. While these theories have been reinforced by more recent studies [ 67 ], in contrast, other authors have shown that DGC is better than SU to select a higher percentage of capacitated sperm [ 68 ] with hyper-activated motion even in cases of subfertility [ 69 ]. Other scientists suggest that neither method provides a cell population with acceptable levels of intact DNA.…”
Section: Classic Methodsmentioning
confidence: 99%
“…The technical parameters of the device were designed to optimize the isolation of motile human spermatozoa with the inflow channel (semen; 100 µm × 50 µm; width × depth), inflow channel (media; 300 µm × 50 µm), common midchannel (laminar flow; 500 µm × 50 µm × 100 mm length). Centrifugation can negatively influence sperm motility [32], mitochondrial function [33], intact acrosomal status [33], and DNA integrity [34]. Using the microfluidic laminar flow and inertia spermatozoa isolation, it was demonstrated that isolated motile spermatozoa had significantly less DNA damage compared to processing sperm with centrifugation, density gradient and centrifugation, and swim-up of overlaid semen [35][36][37].…”
Section: Microfluidics and Potential Use In Spermatozoa Isolation From Noa Testicular Samplesmentioning
confidence: 99%